The Good, the God, and the Ugly: The Role of the Beloved Monster in the Ancient Near East and the Hebrew Bible - Higgins, Ryan S. (Interpretation, 2020)
Ancient Near Eastern texts teem with horrifying and grotesque beings that pose some significant threat to the cosmos, humanity, and its institutions. Adopting Noël Carroll's definition, such beings are monsters: interstitial not only physiologically and ontologically, but also cosmically and morally. This essay takes a comparative and literary approach to beloved monsters in Ugaritic, Mesopotamian, and Hebrew Bible texts. It suggests that in Ugarit and Mesopotamia, such monsters play a crucial role in advancing the goals of antipathic heroes while maintaining the integrity of sympathetic deities. It then considers the beloved monster in the Hebrew Bible and its interpretations. Finally, the essay makes note of the phenomenon's transformation in contemporary speculative fiction. The essay argues that the beloved monster in Ugarit and Mesopotamia keeps together a fragmented cosmos, while in the Hebrew Bible it refracts through the facets in a prismatic God.